Numerical methods for solving temperature and mass transfer simulation on dehydration process of tropical fruits - Alias, Norma; Che Teh, Che Rahim; Berahim, Mazniha; Abdul Ghaffar, Zarith Safiza; Islam, Md. Rajibul; Hamzah, Norhafizah (2009)
Advances in tropical fruit processing and technologies are very significant and efficient in order to reduce post-harvest losses. The dynamic mathematical model of simultaneous heat and moisture transfer is being established for the simulation of temperature and moisture distributions during dehydration potential of foodstuffs in a slab-shaped solid. Mathematical modeling presents the exchange of heat and mass transfer between material and drying air. Finite-difference method (FDM) based on Crank-Nicolson was used to discretise a partial differential equations (PDE) with parabolic type. This paper aims to illustrate the simulation of tropical fruits’ dehydration through some numerical methods such as Jacobi, Gauss-Seidel and Red-Black Gauss-Seidel. This study focuses on the implementation of sequential algorithms on the simulation. 3D geometric visualization by COMSOL Multiphysics and graphical numerical results of FDM approximation in mass and heat transfer demonstrates the results of this research. Most thermal and moisture models are empirical rather than theoretical. However, the best sources of thermal and moisture data for the commercial tropical fruits dehydration derived from the mathematical model in order to avoid high prototype costs, improving inaccurate conditions and processing parameters with the advancement of dryer technologies. The contribution of this paper is to derive the mathematical simulation in representing the actual process of dehydration in foodstuff industry. The computational platform supported by Intel®Core™ based on Quadcore processors and configure with MATLAB software. The performance evaluations of numerical methods are presented in terms of execution time, computational complexity, number of iterations, errors, accuracy and convergence rate. As a conclusion, the temperature and mass transfer generates high significant impact to the efficiency of the dehydration process